PATRONAGE DALAM DENDANG MINANG BASIROMPAK VERSUS BAUWOIK - Maspon Herizal (LP2M ISBI Bandung, 2015)
The purpose of this research is to determine the function of patronage in Basirompak and Bauwoik cases in Payakumbuh. This research applies descriptive-analytical approach undertaken by a systematic procedure. The the theory applied is the decisional theory that explains about thinking concept of culture, music, patronage, and social events. Basirompakand Bauwoik are originatedfrom Payakumbh.The developmentofIslamin thelocal community is not necessarily removing the animistic understanding. This ideology persists in the development of Basirompak and Bawoik inwhich ever show always creates the scary impression especially among women. Such condition affects the psychological community that the existence of Basirompakand Bauwoik become detestable andeventually marginalized from public support. However, the patronage makes Basirompak still be maintained. This is not valid on Bauwoik which gradually becomes drowned and died